Chronic physical exercise alleviates stress-associated amygdala metabolic activity in obese women: A prospective serial 18F-FDG PET/CT study - Pahk, Kisoo; Joung, Chanmin; Kwon, Hyun Woo; Kim, Sungeun (Frontiers in Endocrinology, 2023)
Background: Psychological stress is considered as a major risk factor for cardiovascular disease (CVD). Chronic exercise is known to reduce CVD risk partly through attenuating psychological stress. Obesity has been linked with increased levels of psychological stress. We aimed to prospectively evaluate whether physical exercise could alleviate stress-associated amygdala metabolic activity, assessed by 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) in women with obesity. Material and methods: A total of 43 participants were enrolled in this study. Twenty-three obese women were participated in a physical exercise program 5 days per week for 3 months. The exercise program consisted of aerobic exercise and resistance training. Serial 18F-FDG PET/CT was taken before the start of physical exercise program (baseline) and after finishing the program (post-exercise). A total of 20 participants who underwent 18F-FDG PET/CT for general health check-up were enrolled as non-obese control group. Brain amygdala activity (AmygA) was calculated as maximum standardized uptake value (SUVmax) of amygdala normalized to mean SUV of temporal lobe. Results Chronic physical exercise significantly reduced AmygA and improved body adiposity and systemic inflammation. AmygA was highest in baseline, intermediate in post-exercise, and lowest in non-obese control group (0.76 ± 0.17, 0.61 ± 0.1, 0.52 ± 0.09, p < 0.001). Furthermore, physical exercise also abrogated the association of AmygA with systemic inflammation. Conclusions: Chronic physical exercise reduced stress-associated amygdala metabolic activity and broke its association with systemic inflammation in obese women. This study could explain the putative mechanism underlying the health beneficial effect of exercise on CVD via attenuation of stress neurobiology.